PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN MELALUI MODEL COOPERATIVE LEARNING TIPE STAD PADA SISWA KELAS IV SDN 008 UHAILANU - Taslim; Irfan Dahnial (STKIP Subang, 2026)
This Classroom Action Research (CAR) was motivated by the low learning outcomes and active participation of fourth-grade students at SDN 008 Uhailanu in mathematics, specifically on the topic of fractions. The conventional one-way approach caused students to be trapped in rote learning and feel afraid to ask questions. Therefore, this study aimed to describe the improvement in students' learning outcomes and active participation through the implementation of the Student Teams Achievement Division (STAD) type of Cooperative Learning model. The subjects of the study were 24 fourth-grade students at SDN 008 Uhailanu. The research was conducted in two cycles, following the Kemmis and McTaggart model which includes planning, acting, observing, and reflecting stages. Data were collected using written tests and observation sheets. The results showed a significant improvement. In the pre-cycle, the class average score was only 62.5 with a classical completeness rate of 37.5%. After implementing STAD in Cycle I, the average score increased to 71.5 with a completeness rate of 66.7% and student active participation at 45%. Following guidance adjustments in Cycle II, learning outcomes surged to an average score of 82.5, classical completeness reached 87.5%, and active participation soared to 85%. It can be concluded that the application of the STAD cooperative model is highly effective in overcoming fraction misconceptions, building teamwork (peer tutoring), and meaningfully improving mathematics learning outcomes.